LEITURA E CRÍTICA DO CONHECIMENTO NA CONTEMPORANEIDADE - dos Santos, Paulo Sérgio Nolasco (Organon, 2012)
linked to the intellectual’s role, reading is not only reflection of knowledge power but it is also a remarkable trace of a critical activity, based on the knowledge revision and the definition of these same terms – knowledge, criticism, wisdom. Under the perspective of comparative literature and knowledge production, this article aims at considering the reading nature as a form of knowledge appropriation, to which is supposed within its own exercise and execution currently, the mission of distance and “articulatory” (re)placement from knowledge itself; remodeling it throughout its transformations and through the various nets that comprehend it, particularly when remodeled by the “contemporary view”.